The Added Value of Applying Governance, Risk, and Compliance (GRC) in the Healthcare Sector: A Literature Review - Aldahmashi, Amjad; Abdulsamad, Akram (Advances in Social Sciences Research Journal, 2026)
The healthcare sector faces unique pressures complex regulatory demands, patient safety obligations, escalating cybersecurity threats, and investor expectations making it one of the industries where Governance, Risk, and Compliance (GRC) frameworks offer the greatest potential value. This literature review synthesizes evidence from 25 peer-reviewed studies, systematic reviews, bibliometric analyses, and industry reports published between 2010 and 2026 to answer the question: what added value does applying GRC bring to healthcare organizations? Six distinct value dimensions are identified and examined: (1) firm value and investor confidence, (2) patient safety and care quality, (3) proactive cyber risk management, (4) operational efficiency and cost reduction, (5) regulatory compliance and reputation protection, and (6) strategic resilience and enterprise risk management. Findings indicate that GRC positively affects firm value in healthcare companies, with an explanatory level of 33.8% [14], and that integrated GRC is associated with improved patient safety across multiple health systems [3]. The review also identifies significant barriers to implementation, including cultural resistance, resource constraints, and data privacy concerns, alongside emerging opportunities from artificial intelligence-enabled GRC tools. The evidence consistently demonstrates that GRC value in healthcare is multiplicative rather than additive: governance, risk management, and compliance generate greater combined benefit when integrated than when managed as separate functions.